Impact of corneal cross‐linking on topical drug penetration in humans. (17th November 2014) - Tappeiner, Christoph; Tschopp, Markus; Schuerch, Kaspar; Frueh, Beatrice E.
Abstract Purpose To analyse the influence of corneal cross‐linking (CXL) with ultraviolet‐A (UV‐A) and riboflavin on drug permeability in human subjects. Methods Keratoconus patients (n = 23; mean age 26.9 ± 5.8 years) undergoing a standard CXL procedure with UV‐A (5.4 J/cm2, 30 min) and riboflavin in one eye were included in the study. The pupillary diameter, measured before and every 3 min for 30 min after the topical application of one drop of 2% pilocarpine, was used as an indirect measure of the corneal permeability. The pupillary diameter was measured with an infrared pupillometer device before (baseline) and 4 months after CXL. Results Prior to pilocarpine application, no significant difference in the pupillary diameter was detected before CXL and 4 months later. The mean decrease in the pupillary diameter after the application of pilocarpine was similar at baseline and the 4‐month follow‐up visit: mean decreases of 3.9 and 3.7 mm were observed 30 min after pilocarpine application, respectively (p > 0.05). Conclusions No significant influence of CXL on the corneal penetration of topically applied pilocarpine was observed in this clinical study.